Antibiotic Utilization Pattern in Inpatients of Intensive Care Unit in a Teaching Hospital, Biratnagar, Nepal - Sah, Anil Kumar; Sah, Rubi; Metri, Shashikala; Alam, Kadir; Manandhar, Tyoti Tara (Purbanchal University Health Journal, 2025)
Introduction: Antibiotics were the most often administered medication in intensive care units. In general, the ICU uses antibiotics around ten times more frequently than the hospital's general ward. The majority of patients hospitalized to intensive care units (ICUs) have many problems and are critically unwell and extremely susceptible to infections due to underlying diseases. Objective: The objective of the study is to record antibiotic utilization pattern in ICU Setting. Method: A prospective study was undertaken during the period of March to May 2022. Altogether 140 prescriptions were examined throughout the study period. The study was evaluated using modified International Network for Rational Use of Drugs (INRUD) form. Result: All together total number of patients were 140, among them 83(59.29%) were male and 57(40.71%) were female. Commonly used antibiotic in injection dosage form were cephalosporins group which includes ceftriaxone (16.27%), piperacillin & tazobactam (13.48%) followed by fluroquinolones like levofloxacin (11.39%) and glycopeptides meropenam (7.20%). The current study shows that ceftriaxone (25.58 DDD/100 bed-days) was used most frequently, levofloxacin (6.03) and piperacillin/tazobactam (5.30). Average number of medicine costs were NRS.9149.89. and average costs of antibiotics per patients were NRS 5869.32. Total cost of prescribed antibiotics was NPR 821704.8 Conclusion: Our study demonstrates the high use of antibiotics in the hospital which is nearly 65 percent cost of total medicine. Hence, it needs immediate attention and in order to improve antibiotic use, antibiotic prescribing guideline and stewardship program implementation are highly recommended.